2018
DOI: 10.3122/jabfm.2018.03.170427
|View full text |Cite
|
Sign up to set email alerts
|

Barriers Faced by Family Medicine Graduates Interested in Performing Obstetric Deliveries

Abstract: Fewer family physicians are providing deliveries, which raises concern for access to obstetric care. We found that among recent family medicine graduates who would like to do deliveries, difficulty finding a position that supports including deliveries was a major barrier. (J Am Board Fam Med 2018;31: 332-333.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 2 publications
(1 reference statement)
0
18
0
Order By: Relevance
“…Research studies using data from the Graduate Survey have shown a large gap between practice and preparation 4 with further variation between academic-and community-based programs. 5 Other studies using the data have shown lower odds of burnout with broader scope of practice, 6 state-level variation in burnout, 7 associations between residency training and buprenorphine prescribing, 8 barriers to practicing obstetrics, 9 provision of contraceptive services and abortion care, 10,11 and participation in loan repayment programs. 12 Possible Uses and the Future With multiple years of data, residencies have the capability to identify persistent gaps in their curricula and make changes.…”
Section: Resultsmentioning
confidence: 98%
“…Research studies using data from the Graduate Survey have shown a large gap between practice and preparation 4 with further variation between academic-and community-based programs. 5 Other studies using the data have shown lower odds of burnout with broader scope of practice, 6 state-level variation in burnout, 7 associations between residency training and buprenorphine prescribing, 8 barriers to practicing obstetrics, 9 provision of contraceptive services and abortion care, 10,11 and participation in loan repayment programs. 12 Possible Uses and the Future With multiple years of data, residencies have the capability to identify persistent gaps in their curricula and make changes.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, the proportion of family physicians practicing obstetrics is rapidly declining, despite findings that their outcomes are similar to those of obstetricians. Barreto et al 35 analyzed data from the 2016 Family Medicine National Graduate Survey (n ϭ 2018) to determine the extent and barriers to obstetric practice. Two barriers to providing obstetrics care were given by over half of the 865 new family physicians interested in delivering babies: 1) obstetrics was not available in their practice; and 2) lifestyle considerations.…”
Section: Agents Of Primary Care Implementationmentioning
confidence: 99%
“…Contrary to previous research,10 15 of 2013 family medicine residency graduates who were interested in delivering babies but who were not doing so in practice 3 years later (n=856), few reported malpractice costs (24%) or privileging challenges (15%) as barriers to doing deliveries. However, 60% indicated that there was no opportunity to do deliveries in the practice they joined,16 raising questions about constraints placed on family physicians by employers or hospitals.…”
Section: Introductionmentioning
confidence: 99%